Relationship of Stress Levels in Alcohol Abuse in Teenager: A Literature Review - Jennifa Jennifa; Nessy Anggun Primasari; Eltanina Ulfameytalia Dewi; Rista Islamarida (Universitas Bondowoso, 2021)
Introduction: Adolescents are individuals who experience a period of transition from childhood to adulthood. The inability of adolescents to control their emotions often leads to deviant behavior. Alcohol consumption behavior is currently a growing problem in the world of adolescents. Alcohol abuse occurs because alcohol is used to overcome psychological problems and stress in their lives, a person consumes alcohol as a way to escape because drunkenness makes it easy to forget the problem. This is dangerous because it can lead to alcoholism or dependence. Method: This writing uses a systematic review design. The data is taken from the science direct, proquest and google cendikia databases, with a period of 2016-2020. Search for journals and articles using the keywords Result: It was found that there is a significant relationship between stress levels experienced by adolescents and alcohol abuse. Because teenagers can not solve the problems they face so that it has a negative impact on alcohol consumption. Conclusion: Teenagers can be quickly influenced by negative things, especially from a bad environment, so that in the search for articles, more teenagers have problems from their families so that stress levels are higher. So there needs to be a role for parents in overcoming the bad effects of stress experienced by teenagers.